Multi-slice helical CT: Scan and reconstruction - Hu, Hui (Medical physics (Lancaster), 1999)
The multi-slice CT scanner refers to a special CT system equipped with a multiple-row detector array to simultaneously collect data at different slice locations. The multi-slice CT scanner has the capability of rapidly scanning large longitudinal (z) volume with high z-axis resolution. It also presents new challenges and new characteristics. In this paper, we study the scan and reconstruction principles of the multi-slice helical CT in general and the 4-slice helical CT in particular. The multi-slice helical computed tomography consists of the following three key components: the preferred helical pitches for efficient z sampling in data collection and better artifact control; the new helical interpolation algorithms to correct for fast simultaneous patient translation; and the z-filtering reconstruction for providing multiple tradeoffs of the slice thickness, image noise and artifacts to suit for different application requirements. The concept of the preferred helical pitch is discussed with a newly proposed z sampling analysis. New helical reconstruction algorithms and z-filtering reconstruction are developed for multi-slice CT in general. Furthermore, the theoretical models of slice profile and image noise are established for multi-slice helical CT. For 4-slice helical CT in particular, preferred helical pitches are discussed. Special reconstruction algorithms are developed. Slice profiles, image noises, and artifacts of 4-slice helical CT are studied and compared with single slice helical CT. The results show that the slice profile, image artifacts, and noise exhibit performance peaks or valleys at certain helical pitches in the multi-slice CT, whereas in the single-slice CT the image noise remains unchanged and the slice profile and image artifacts steadily deteriorate with helical pitch. The study indicates that the 4-slice helical CT can provide equivalent image quality at 2 to 3 times the volume coverage speed of the single slice helical CT.